Improved Low Concentration Water Content Detection in Biodiesel utilizing Phase Shift-Based Capacitive Method - Azmi bin Mohamed, Suriani binti Abu Bakar, Illyas bin Md Isa (Tanjung Malim, 2024)
Improved Low Concentration Water Content Detection in Biodiesel utilizing Phase Shift-Based Capacitive Method by Azmi bin Mohamed, Suriani binti Abu Bakar, Illyas bin Md Isa